Field Emergence and Seed Vigor Sensitivity of Special Purpose Rice (Oryza sativa L.) Irradiated with Gamma Rays - Dela Cruz, Leah; Paulina Justo Alvaran; Elmer Padilla Natividad Jr. (Journal of Science and Technology, 2024)
Special purpose rice (SPR) are varieties with notable features such as aroma, grain color and eating quality. Lower yield is one of the challenges in the production of SPR which this study ultimately aimed to address by developing mutant varieties with higher yields and good eating quality. In the process of obtaining desirable mutants through gamma irradiation, different doses were applied which could negatively affect the germination and seed vigor of the irradiated seeds. Thus, the responses of four newly-developed special purpose rice varieties to different irradiation doses were evaluated in terms of field emergence and seed vigor. Five irradiation doses of gamma rays were used, namely: 0 Gy (control), 150 Gy, 200 Gy, 250 Gy and 300 Gy using the Ob-Servo Sanguis Co-60 Irradiation facility at the Philippine Nuclear Research Institute (PNRI). The study was laid out in the open field following the Complete Randomized Design arrangement with four replications. Results indicated that irradiation doses of 150 to 300 Gy resulted to significantly lower field emergence and seed vigor when compared to the untreated seeds but the reduced levels of field emergence ranging from 89.60 to 92.97% were still within the acceptable minimum level of germination percentage which is 80%. Among the varieties/line tested and within the range of doses studied, it appeared that CLS 4, with waxy endosperm, was relatively more sensitive to irradiation treatment in terms of field emergence and seed vigor.